2018
DOI: 10.1155/2018/6579894
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure due to a Tobramycin and Vancomycin Spacer in Revision Two-Staged Knee Arthroplasty

Abstract: Two-stage revision total knee arthroplasty (TKA) is the standard of care for prosthetic joint infections. The first stage involves removal of the infected prosthesis and placement of an antibiotic impregnated cement spacer; following a period ranging from 4 weeks to 6 months, the spacer is then removed and replaced with a permanent prosthesis. The advantage to this approach is that antibiotic impregnated spacers provide supratherapeutic levels in the joint without toxic accumulation in serum. However, it remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Additionally, it is possible to introduce as much as 10-12 g of antibiotics in 1 bag of bone cement, but >4.5 g of antibiotics per bag of bone cement will decrease the mechanical properties of a standard prosthesis [ 23 ]. Although there is no consensus as to the optimal range for antibiotic-loaded bone cement in spacers, several case reports suggesting a dose-dependent risk of acute kidney injury (AKI) from surgeon-made antibiotic spacers utilizing aminoglycosides have been described [ 24 , 25 ]. In a study by Menge et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is possible to introduce as much as 10-12 g of antibiotics in 1 bag of bone cement, but >4.5 g of antibiotics per bag of bone cement will decrease the mechanical properties of a standard prosthesis [ 23 ]. Although there is no consensus as to the optimal range for antibiotic-loaded bone cement in spacers, several case reports suggesting a dose-dependent risk of acute kidney injury (AKI) from surgeon-made antibiotic spacers utilizing aminoglycosides have been described [ 24 , 25 ]. In a study by Menge et al.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum creatinine above 50% from normal has been reported in 20% of patients with tobramycin-impregnated spacer during the first postoperative week after the first-stage surgery [66]. Underlying renal dysfunction predisposes to ALCS-related nephrotoxicity [64][65][66]. However, other studies support that the high levels of the antibiotics observed immediately after spacer implantation return to normal within 24 hours, therefore systemic side effects are not a potential risk for the patient [9,41,42].…”
Section: Complications Of Alcsmentioning
confidence: 99%
“…Older patients are probably more prone to such complications [ 38 ]. Occasionally, removal of the ALCS is mandatory to restore renal function [ 8 , 59 , 64 , 65 ]. Increased serum creatinine above 50% from normal has been reported in 20% of patients with tobramycin-impregnated spacer during the first postoperative week after the first-stage surgery [ 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…Complications include hepatotoxicity and bone marrow depression following gentamicin plus vancomycin plus cefotaxime hip spacer implantation,6 allergic reactions with tobramycin plus vancomycin impregnated hip spacer7 8 and commonly acute kidney injury (AKI) or acute renal failure (ARF) with the use of aminoglycosides alone or in combination with vancomycin. Several published case reports describe ALBC-related AKI,9–19 with most patients requiring haemodialysis and spacer explantation 9 13 15 17 20–22. This is an additional case of AKI attributed to the systemic absorption of an aminoglycoside following implantation of ALBC and beads with recovery of renal function following explantation of the tobramycin cement spacer and beads, thus preventing haemodialysis.…”
Section: Introductionmentioning
confidence: 99%